The contribution of aeolian sand and dust to iron fertilization of phytoplankton blooms in southwestern Ross Sea, Antarctica. Issue 4 (24th April 2014) - Winton, V. H. L.; Dunbar, G. B.; Bertler, N. A. N.; Millet, M.‐A.; Delmonte, B.; Atkins, C. B.; Chewings, J. M.; Andersson, P.
Abstract Iron is a limiting micronutrient for primary production in the Ross Sea, Antarctica. Recent observations reveal low dissolved Fe (dFe) concentrations in the Ross Sea polynya following high initial rates of primary production in summer, after the dFe winter reserve has been consumed. Significant new sources of dFe are therefore required to further sustain phytoplankton blooms. Iron from aeolian sand and dust (ASD) released from melting sea ice is one potential source. To constrain aeolian Fe inputs, we determined ASD mass accumulation rates and the total and soluble Fe content of ASD on sea ice in McMurdo Sound, southwestern (SW) Ross Sea. The mean mass accumulation rate was 1.5 g m−2 yr−1, total Fe content of this ASD was 4 ± 1 wt %, and the percentage of soluble Fe was 11 ± 1%. Our mean estimate of the bulk aeolian dFe flux of 122.1 µmol m−2 yr−1 for the McMurdo Sound region suggests that aeolian Fe can support between 9.0 × 109 and 4.1 × 1011 mol C yr−1 (0.1–4.9 Tg C yr−1) of new primary production. This equates to only 15% of new primary production in the SW Ross Sea, suggesting that aeolian dFe is a minor component of seasonal Fe supply. The very high ASD accumulation on sea ice in McMurdo Sound compared to other regions of Antarctica suggests that our results represent the upper limit of dFe supply to the ocean from this source in the Ross Sea.